PERANCANGAN PROMOSI KERAJINAN ADID FURNITURE MELALUI MEDIA WEBSITE - BAYU ADITYA MYEVA, Dra. Jupriani, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The times now it makes the taste of the public who need furniture items has been changed, the current society tends to be more interested in the more modern furniture items and unique. Rattan wicker products industry had raised the name of West Sumatra as a manufacturer of first-class rattan weave the present nationwide. In recent years the potential of rattan handicraft has decreased due to the decline in demand from consumers and compete with similar products from other regions.The purpose of this website is the design as media promotion of Adid Furniture are expected to reach a broader maket so that it can enter the global market and also provide consumer convenience in getting information or new products, promotional media provide more easily in the system of sales promotion with marketing or selling a product in a virtual world and also to increase the formation about the existence of the company. In designing this website author using the method of 5W1H (what, where, who, why, how). The advantages of media website in this promotion can also be carried faster more clear by looking at the components that are on the website.The existence of this Furniture Adid website is expected to push the company expanded rapidly in increasing sales with promotional media so that it can enter the global market and lifting the industry’s potential to come back into the wicker industry the flagship. As a study in designing website and supported by media advocates be dress shirts, pillows, flyer, key chains, business cards, posters and stickers that are capable of promoting websites Adid Furniture.Keyword : Website, Promotion Media, Craft, Ratan Wicker